Analysis of free space optics link availability with real data measurement in tropical weather - Ahmad Zabidi, Suriza; Islam, Md. Rafiqul; Wajdi, Al Khateeb (2015)
Free Space Optical communications (FSO) have attracted a lot of attention for a variety of applications in telecommunications field. The unlicensed, higher speed, broader and unlimited bandwidth, low cost solutions, and shortest deployment period are some of the drives to deploy FSO. However, weather attenuation has a big impact on the transmission line of FSO. In temperate region a thorough studies are available on the link availability due to weather effect. In tropical region however most FSO links install especially in Malaysia are as a backup system. There is no analysis on the FSO link availability under tropical weather condition. Therefore, the objective of this paper is to provide an analysis on the FSO link availability with real data measured in tropical weather condition. Based on one year measurement of rain attenuation and rain intensity, link availability of 99.99% can be achieved for a link distance of 1.25km and fade margin of 25dB. The outcome of this research is expected to give a foundation for the design and development of a long range FSO link under tropical weather condition.